The C20 highly branched isoprenoid biomarker – A new diatom-sourced proxy for summer trophic conditions?. (April 2015) - Muschitiello, Francesco; Andersson, August; Wohlfarth, Barbara; Smittenberg, Rienk H.
Highlights: C20 HBI biomarker in freshwater sediments produced by a specific diatom taxon. The biomarker can be used to reconstruct past trophic conditions of the lake. The biomarker reflects environmental conditions during the dry season. Abstract: The exact biological source of the C20 highly branched isoprenoid (HBI) present in sediments from aquatic systems is unclear. We therefore examined the relationship between the distribution of fossil diatoms and the concentration of the C20 HBI in a Late Glacial sedimentary record from the Hässeldala Port paleolake in southern Sweden. Using Bayesian multiple linear regression analysis, we show that its concentration is linked primarily to the production of the diatom taxon Gomphonema acuminatum, which accounts for the largest proportion of the temporal variability in the biomarker. By analogy with modern observations, we argue that an increasing amount of G. acuminatum biomass in our sedimentary record reflects increasing oligotrophy in the paleolake during the summer growing season, especially at times defined by subdued hydrologic flow. Our conclusions are corroborated by the δ 13 C composition of the C20 HBI biomarker, which points to a negative photosynthetic fractionation between atmospheric CO2 and the pool of dissolved inorganic carbon during diatom bloom, a distinct phenomenon at times of inhibited hydrological flow. Accordingly, we suggest that the C20 HBI biomarker can be effectively used to reconstruct the trophic state of the paleolake at Hässeldala Port, while its stable isotope composition can provide physicochemical information about the lake conditions during the dry summer season. Moreover, we note that the major hydrological shifts recorded in the G. acuminatum -C20 HBI stratigraphy do not coincide with the pollen zone boundaries. We thus infer that aquatic and terrestrial environmental responses to climate change are substantially decoupled through the hydrological system, which highlights the necessity for multi-proxy investigations to decipher past climate events.